Competition Registration and Announcement Platform Based on Node.js and .NET Core Web API Development - Zhang, Yuanyuan (International Journal of Computer Science and Information Technology, 2024)
In this project, the front-end is developed using the Vue template engine based on Node.js and the Element UI component library, while the back-end is built with .NET Core Web API. SQL Server is used as the database. The system’s front-end is primarily designed for use by regular users, including both teachers and students, who can log in only after applying for registration and passing approval. Regular users have access to various modules, such as the event release module, research project module, news information module, notice module, and personal center module. On the back-end, administrators have access to several management functions, including competition module management, team module management, research module management, system module management, user module management, and achievement module management. The event registration and announcement platform streamline communication and reduces costs for teachers and students in the team formation process by centralizing the management of events and projects, which are typically difficult to oversee. Additionally, it allows users to independently maintain event and project information, reducing the workload for platform operators.